Germination, vigour and dehydrogenase activity of naturally aged rice (Oryza sativa L.) seeds soaked in potassium and phosphorus salts - Bam, R.K.; Kumaga, F.K.; Ofori, K.; Asiedu, E.A. (Asian Journal of Plant Sciences, 2006)
The effectiveness of different concentrations of potassium and phosphorus salts and the duration of soaking on germination, vigour and dehydrogenase activity of rice seed, cvr IDSA 85, was studied in the laboratory. Treatments comprised untreated control, soaking in KCL at K concentrations of 0.5, 1.0%, 1.5 and 2.0% w/v and in KH2PO4 at P concentrations of 0.05, 0.1, 0.2, 0.3, 0.4 and 0.5% w/v and water for 12 or 24 h. Soaking seeds in P for 24 h increased germination capacity (p = 0.013) from 79% in the control to 94% in 0.5% P for 24 h. Irrespective of the soaking medium, soaking duration did not increase germination capacity. Germination energy increased from 28% in the control to 77% in water, 83% in 0.5% K and 89% in 0.2% P. Soaking IDSA 85 seeds in K and P solutions or water significantly reduced the mean germination time and increased the daily rate of seedling emergence. Seeds soaked in P and K solutions produced significantly taller plants than the untreated control and water. Seeds soaked in KCL or KH2PO4 solutions had higher dehydrogenase activity compared to water suggesting higher viability and vigour of seeds soaked in K and P solutions. © 2006 Asian Network for Scientific Information.
Keywords: Dehydrogenase activity; Germination capacity; Germination energy; Mean germination time; Oryza sativa